Enhancing and diversifying ATMA’s databases to ensure sustainability - Supyan Hussin,; Ding, Choo Ming (Universiti Kebangsaan Malaysia, 2004)
Following the increased interest in the Malay World studies world wide, and a change in ATMA’s directorship in April 1999, we had, for the first time in UKM history, the chance to design our databases. After creating the first database, PADAT, we have successfully created new supplementary or complimentary databases. They are constructed not only to satisfy demands, but also to whet new appetite. Our achievements thus far are the result of an efficient working team, a visionary leadership and overwhelming support from UKM’s top management. We hope to develop our databases to meet world standards, and in doing so, to make ATMA to become another defining point in the study of the Malay world. In order to create a circle of sustainability, we must in turn convince paying users that their expenditure will benefit them. As researchers get used to faster computers and become more impatient, the pressures on databases increases. The right information must be quickly accessible and at any given time